UniKL MIIT SMART UniCafe System - Ainnur Athirah binti Munir; Robiah binti Hamzah (Journal of Computing Technologies and Creative Content, 2023)
This paper presents the development of the SMART UniCafe System—a web-based platform aimed at improving the food ordering system experience in UniKL MIIT cafeterias. The system addresses challenges such as manual ordering processes, unorganized order management, limited payment options, and lack of time estimation. XAMPP, MySQL, Visual Studio Code, and Draw.io were utilized in the development process. The objectives were to create a user-friendly web interface, improve the efficiency of the food ordering process, and enhance customer satisfaction. The SMART UniCafe System aims to revolutionize the dining experience by providing a seamless and user-friendly platform for customers, sellers, and administrators. The findings presented in this paper serve as a foundation for future updates to meet evolving user needs and remain competitive in the market. With the recommended improvements, the system has the potential to transform cafeteria dining into a more streamlined and convenient process.